Effects of vitamin E on growth, survival and fecundity of zebrafish (Danio rerio) (African Journal of Fisheries Science, 2015)
The aim of this study was to evaluate the effects of dietary vitamin E (α-tocopherol) in 4 levels (100, 300, 500 and 1000 mg ascorbic acid kg-1) with 1 control group (0 mg kg-1) on growth, survival, fecundity and egg diameter in the zebrafish, Danio rerio. Zebrafish were divided into 5 treatments each triplicated, and fed with one of the five diets for 20 weeks. There were no significant differences in egg diameter observed between the treatments. The survival rate of zebrafish fed the diet containing 1000 mg kg-1 vitamin E was higher than other groups. In the vitamin E treatments, the body weight increase (BWI), specific growth rate (SGR) and fecundity of zebrafish increased significantly with increasing levels of vitamin E (P < 0.05). The significance of the results herein obtained underlined the importance of diet in the reproductive process, supporting the hypothesis that feed additives can improve fecundity. Considering that the zebrafish has been clearly established as a vertebrate model for biomedical research, these results support the potentiality of feed additives such as vitamins can improve reproduction in all vertebrates, including humans.